PENGARUH TINGKAT PENDIDIKAN ORANG TUA TERHADAP PERILAKU SOSIAL ANAK TK RAUDHATUL JANNAH - Putri Clawson; Anita Febriani (P3M STKIP 'Aisyiyah Riau, 2017)
In this study the method used is correlation, which is a method to provide a clear and accurate picture of the problem being examined. This research is not directed at testing hypotheses, but directed at describing variables or conditions as they are in a situation. this is in accordance with the opinion of Arikunto (2002: 131). The results of parental responses to the social behavior of children in kindergarten Raudhatul Jannah, in terms of overall indicators of parental responses to social behavior of children classified as